Sonography assisted clot evacuation in early intracerebral haemorrhage - Gene, Teo Eu (2020)
Spontaneous intracerebral haemorrhages (ICH) are an increasingly common condition that leads to severe morbidities and mortality. Early surgical evacuation of spontaneous supratentorial ICHs has not consistently been proven to be beneficial from multiple studies. We investigate the effectiveness of ultrasound guided early surgical evacuation of spontaneous supratentorial ICHs with respect to the completeness of evacuation on radiological evaluation. We prospectively recruited 58 patients who presented to a tertiary Neurosurgery centre in Malaysia within 48 hours of ictus for a spontaneous supratentorial ICH and underwent surgical evacuation of clot between June 2017 to February 2019. The patients were randomly assigned to surgical evacuation of clot with or without intraoperative ultrasound guidance in 1:1 ratio. Pre operative and immediate post operative CT brain images were compared. The primary outcome was the completeness of clot evacuation measured via the (a x b x c)/2 formula. The patient or their family underwent a telephone interview 3 months post surgery to assess neurological outcome. 29 patients were randomly assigned to both early surgical evacuation of clot with and without intraoperative ultrasound guidance. All patients were followed up at 3 months. Patients in the surgical evacuation with intraoperative ultrasound guidance and without intraoperative ultrasound guidance had mean reductions of 88.7% and 86.9% respectively, which was statistically significant, p value = 0.022. Mortality rate at 3 months for both groups was 10.3% and 20.1% respectively. (OR 2.3, 95% CI 0.51 to 10.08; p = 0.285). Conclusion Ultrasound guided evacuation of spontaneous supratentorial ICHs increases the completeness of clot evacuation via radiological evaluation.